A Study of Jordanian Proverbs Related to the Parts of the Body - Khalifeh, Abeer; Rababah, Luqman (Journal for the Study of English Linguistics, 2022)
The present study focuses on studying body-related proverbs in Jordan. The study uses a descriptive research design to examine the organization and construction of 45 Jordanian proverbs about bodily parts in order to come up with a set of conclusions. First, Jordanian proverbs and idioms about humans’ bodily parts are divided into five categories: (i) Proverbs/ idioms concerning relative relationships and marriage advice, (ii) Proverbs/ idioms concerning friendships and strangers (iii) Proverbs/idioms expressing a person’s traits, (iv) Imparting guidance, and satisfaction with life (v) Proverbs/ idioms related to body organs associated with food.